Photonics for radar networks and electronic warfare systems - Bogoni, Antonella; Ghelfi, Paolo; Laghezza, Francesco (The Institution of Engineering and Technology, 2019)
This book outlines the potential for microwave photonics in radar and electronic warfare systems, covering basic concepts and functions, comparing performance with conventional systems, describing its impact on digital signal processing, and exploring integration issues.
Keywords: Photonics -- Military aspects.; Radar -- Military applications.; Electronics in military engineering.; elektronické knihy; electronic books